Online Media and Establishment of Religious Understanding of the Madrasah Aliyah Students in Gorontalo - Arafah, Sitti; Basman, Basman; Nisa’ , Khaerun; Abubakar, Asnandar (Proceedings of International Conference on Da'wa and Communication, 2020)
This research is a qualitative descriptive study that aims to describe the religious understanding of Madrasah Aliyah (MA) students in Gorontalo obtained from online media. It was also conducted to determine the school's response in harmonizing religious understanding. This study aims to answer the following questions: (1) How is the religious understanding of Madrasah Aliyah students obtained through online media? and (2) How do the schools respond and harmonize the religious understanding of students who interact with online religious sites? Data were collected through observation, interviews, and documents study, by targeting Madrasah Aliyah students, teachers, religious leaders, academics, and community leaders. The results showed that MA students use online media as sources of learning materials and religious content with the duration of accessing online media reaching 4 to 10 hours per day. It has influenced the understanding, attitudes, and religious practices of MA students. The understanding and practice of "exclusive" religion have become widespread, among students no longer celebrating the Prophet's birthday (mawlid), barzanji, tahlil, prohibiting to wish someone Merry Christmas, forbidding music, forbidding to take self pictures, and considering the traditions of the Gorontalo people which aren't following Islamic values as heretical and forbidden. As a response to dealing with the problems above, the school tries to align students' religious understanding by strengthening religious moderation for teachers and students, building communication with students in social media, and providing mentors for students. This study recommends: (1) the importance of strengthening the understanding of religious moderation to teachers and students, (2) encourage religious institutions such as NU and Muhammadiyah to use online media as a da'wah tool, and use language that easy to understand by the millennial generation.